Capacitance properties of nano-structure controlled alumina on polymer substrate - Jung, S.-W.; Min, H.-S.; Han, J.W.; Lee, J.-K. (Materials Research Society of Korea, 2007)
Embedded capacitor technology can improve electrical performance and reduce assembly cost compared with traditional discrete capacitor technology. To improve the capacitance density of the Al2O3 based embedded capacitor on Cu cladded fiber reinforced plastics (FR-4), the specific surface area of the Al2O3 thin films was enlarged and their surface morphologies were controlled by anodization process parameters. From I-V characteristics, it was found that breakdown voltage and leakage current were 23 V and 1× 10-6 A/cm2 at 3.3 V, respectively. We have also measured C-V characteristics of Pt/Al2O3/Al/Ti structure on Cu/FR4. The capacitance density was 300 nF/cm2 and the dielectric loss was 0.04. This nano-porous Al2O3 is a good material candidate for the embedded capacitor application for electronic products.